2022
DOI: 10.1021/acssuschemeng.2c03405
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Chemical Synthesis of Valuable Fuels and Chemicals from n-Hexane and Its Mixture with Methanol and Ethanol

Abstract: Among several emerging technologies that are focused on finding sustainable routes for reforming heavy oils and/or alcohols into valuable fuels and complex chemicals, nonthermal plasma shows promise both due to its non-equilibrium nature and its ability to use intermittent renewable electricity. In this work, we investigate its interaction with organic compounds as a "green" process for simultaneously synthesizing hydrogen, cracking heavy oils, and producing more valuable, complex chemicals. A pin-to-plate mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Furthermore, using a simple amine can alleviate the requirement of high pressure and temperature for synthesizing higher-order amines, cutting down the energy costs. As reported in our group's earlier paper, 21 we observed that a low temperature of −20 °C increases the production efficiency of liquid products significantly as opposed to room temperature, and thus, it was maintained across all studies except when we studied the effect of temperature. Different operating conditions are investigated to control or induce the reaction chemistry, knowing which, our proposed reactor could potentially be a sustainable alternative to the current NOC synthesis methods, for e.g., the Schiff base reaction for amination.…”
Section: ■ Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, using a simple amine can alleviate the requirement of high pressure and temperature for synthesizing higher-order amines, cutting down the energy costs. As reported in our group's earlier paper, 21 we observed that a low temperature of −20 °C increases the production efficiency of liquid products significantly as opposed to room temperature, and thus, it was maintained across all studies except when we studied the effect of temperature. Different operating conditions are investigated to control or induce the reaction chemistry, knowing which, our proposed reactor could potentially be a sustainable alternative to the current NOC synthesis methods, for e.g., the Schiff base reaction for amination.…”
Section: ■ Introductionsupporting
confidence: 80%
“…In this regard, non-thermal plasma (NTP) can prove to be a notable solution, owing to its previous use in different fuel-reforming studies involving various carbon sources like alcohols, hydrocarbons, and a mixture of both . NTP has the ability to produce highly energetic electrons at ambient temperature and pressure conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The microsecond pulsed DBD reactor used in this contribution was describe before by Banerjee et al [12] and is shown in Fig. 1.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study on a dielectric barrier discharge (DBD) reactor at the McGill PCPL laboratory was conducted by Banerjee et al [12]. A pin and plate NTP was ignited directly over different hexane-based mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with the carbon-neutral goal of UNFCCC, it is crucial to seek renewable and sustainable technologies such as electrocatalysis, photocatalysis, nonthermal plasma, and membrane separation to address the dilemma. Among them, the photocatalysis process has appeared as a potent alternative to yield carbon fuels, which is known for its mild operating conditions. It is a sustainable process by utilizing atmospheric CO 2 waste as the raw material and inexhaustible sunlight as the primary driving energy .…”
Section: Introductionmentioning
confidence: 99%